Hydrogen-resistant coating for high-pressure hydrogen transmission titanium alloy pipeline and preparation method of hydrogen-resistant coating

By combining the Ni buffer layer, NiP-metal oxide composite plating, Ni-graphene oxide layer and oxide ceramic layer on the titanium alloy matrix, the problems of poor bonding strength and hydrogen permeation of hydrogen resistance composite coating of the titanium alloy matrix are solved, and the problems of hydrogen permeability of hydrogen resistance composite coating of the titanium alloy matrix are achieved. It has efficient hydrogen barrier and long-life hydrogen barrier coating, which meets the safety and industrial promotion requirements of high-pressure hydrogen transmission pipelines.

CN119144957APending Publication Date: 2024-12-17LIAOCHENG ANTAI PETROLEUM MACHINERY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411658425.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the prior art, the hydrogen-resistance composite coating of the titanium alloy matrix has poor bond strength, and hydrogen permeation in high-pressure hydrogen environment leads to hydrogen embrittlement problems. The hydrogen-resistance coating has a short service life and high cost, making it difficult to meet the safety of the subsea high-pressure hydrogen transmission pipeline. and service life requirements.

Method used

The combined structure of Ni buffer layer, NiP-metal oxide composite plating, Ni-graphene oxide layer and oxide ceramic layer is used to prepare hydrogen-resistance coating through PVD, chemical electroplating, laser cladding and magnetron cosputtering technology. Improve the hydrogen resistance and bonding strength of the coating and reduce porosity.

Benefits of technology

It significantly improves the hydrogen resistance efficiency and binding force of the hydrogen resistance coating, extends the service life of high-pressure hydrogen transmission pipelines, reduces costs, and meets the industrial application needs of high-pressure hydrogen transmission pipelines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144957A_ABST
    Figure CN119144957A_ABST
Patent Text Reader

Abstract

The invention relates to a hydrogen-resistant coating for a high-pressure hydrogen transmission titanium alloy pipeline and a preparation method of the hydrogen-resistant coating, and belongs to the technical field of hydrogen-resistant coating preparation. According to the scheme, the Ni buffer layer, the NiP-metal oxide composite coating, the Ni-graphene oxide layer and the oxide ceramic layer are prepared for the high-pressure hydrogen conveying pipeline with the titanium alloy as the base body, the porosity can be reduced through the Ni-graphene oxide layer, the hydrogen resistance of the coating is improved, and the corrosion resistance of the coating is improved. Meanwhile, the oxide ceramic layer and the NiP-metal oxide composite coating which are low in hydrogen permeability coefficient are selected as the hydrogen blocking layer, the hydrogen blocking efficiency of the coating can be greatly improved, the hole sealing effect is achieved, the pure Ni buffer layer can achieve the buffer effect, the bonding strength of the coating and a titanium alloy matrix is improved, the porosity can be reduced, and the hydrogen blocking performance is further improved; the hydrogen-resistant coating is high in binding force with the titanium alloy matrix and excellent in hydrogen permeation resistance, can fully meet the industrial application requirement of the high-pressure hydrogen conveying pipeline, and has a good industrial popularization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline and a preparation method thereof, belonging to the technical field of hydrogen barrier coating preparation. Background Art

[0002] As a new type of energy, hydrogen energy has the advantages of wide sources, no pollution, and recyclable and renewable. Pipeline transportation of hydrogen is an important part of the development of hydrogen energy. The current problems of hydrogen embrittlement and corrosion in hydrogen transportation pipelines cannot be underestimated, which will directly lead to severe challenges to the safety of hydrogen pipeline transportation and service life. Since hydrogen has an extremely small atomic radius, it has a strong ability to penetrate and diffuse in metal materials. The penetration of hydrogen will cause hydrogen embrittlement and hydrogen corrosion in metal materials, which will greatly shorten the service life of metal materials. In addition, the impact of high pressure on hydrogen barrier coatings during hydrogen pipeline transportation is also a severe challenge that is easily overlooked.

[0003] In the existing technology, hydrogen barrier coatings are mainly divided into four categories: 1) oxide ceramic coatings mainly composed of Al2O3, Cr2O3, YSZ, and Er2O3; 2) silicide ceramic coatings mainly composed of Si3N4 and SiC; 3) titanium-based ceramic coatings such as TiN and TiC; 4) aluminide coatings mainly composed of FeAl. However, the hydrogen barrier effect of a single-layer hydrogen barrier coating is limited, and the coating is easily damaged. After the coating is damaged, pores will appear, which will cause the hydrogen barrier effect to be sharply weakened. Therefore, the research on hydrogen barrier composite coatings is currently a hot topic.

[0004] High-pressure hydrogen storage and transmission are important links in the development of hydrogen energy industrialization. In the existing technology, stainless steel substrates are often used for the construction of high-pressure hydrogen systems. Stainless steel has excellent corrosion resistance and plasticity. In the transportation of high-pressure hydrogen on the seabed, titanium alloys have better corrosion resistance than stainless steel. The high-pressure hydrogen environment will also cause hydrogen embrittlement of titanium alloy hydrogen pipelines due to the diffusion of hydrogen. Therefore, how to effectively prevent hydrogen from penetrating into the interior of the titanium alloy metal and causing hydrogen embrittlement is a technical problem that needs to be solved urgently. However, there are few studies on hydrogen barrier composite coatings for titanium alloy substrates, especially the bonding strength between the titanium alloy substrate and the hydrogen barrier composite coating. However, due to the working environment of submarine hydrogen transmission, there is no need to pay extra attention to the high temperature resistance of the hydrogen barrier composite coating. In addition, the research on hydrogen barrier composite coatings has become a hot topic at present. Although the composite coating has little advantage over the single-layer coating in terms of preparation process and cost, the hydrogen barrier coatings for submarine hydrogen pipelines have very high installation, replacement and maintenance costs, so the service life of the pipes after laying is required to be higher. This requires the development of hydrogen barrier composite coatings with excellent hydrogen barrier effect and longer service life.

[0005] In the Chinese patent CN116043200A, the invention name is a method for preparing a nickel-phosphorus-based hydrogen barrier composite coating, a nickel-phosphorus-based hydrogen barrier composite coating prepared by a chemical electroplating method is disclosed. This new nickel-phosphorus-based alloy coating has the advantages of good hydrogen barrier performance and long service life as a hydrogen barrier coating, which can effectively reduce the penetration of hydrogen into the pipeline, thereby ensuring the safe operation of hydrogen-related pipelines. However, the substrate of the hydrogen barrier composite coating is X65 pipeline steel. When the titanium alloy is used as the substrate, there is a problem of poor bonding strength. The bonding strength is closely related to the service life of the coating and the difficulty of pipe transportation conditions. It is a performance indicator that needs to be focused on. In addition, the surface of the titanium alloy pipe is prone to oxide scale, which will also cause the bonding strength of the composite coating to deteriorate and affect the hydrogen barrier performance of the composite coating. In addition, the hydrogen barrier performance of the hydrogen barrier composite coating needs to be improved.

[0006] Therefore, it is necessary to develop a hydrogen barrier coating suitable for titanium alloy pipelines for hydrogen transportation under high-pressure conditions, which is resistant to hydrogen penetration, suitable for high-pressure hydrogen environments and has good titanium alloy bonding strength. This is crucial to ensure the safety and service life of titanium alloy pipelines for hydrogen transportation, thereby meeting the needs of submarine high-pressure hydrogen transportation. Summary of the invention

[0007] In order to solve the above problems, a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline and a preparation method thereof are provided. For a high-pressure hydrogen transmission pipeline with a titanium alloy as a substrate, a Ni buffer layer, a NiP-metal oxide composite coating, a Ni-graphene oxide layer and an oxide ceramic layer are prepared respectively. The Ni-graphene oxide layer can reduce the porosity and improve the hydrogen barrier performance of the coating. At the same time, an oxide ceramic layer with a low hydrogen permeability coefficient and a NiP-metal oxide composite coating are selected as the hydrogen barrier layer, which can greatly improve the hydrogen barrier efficiency of the coating and play a role in sealing the pores. The pure Ni buffer layer can not only play a buffering role to improve the bonding strength between the coating and the titanium alloy substrate, but also reduce the porosity to further improve the hydrogen barrier performance. The hydrogen barrier coating can effectively solve the problem that the current organic or inorganic hydrogen barrier coating cannot provide long-term protection or has poor hydrogen permeation resistance. The prepared hydrogen barrier coating has high bonding strength and excellent hydrogen permeation resistance, can fully meet the industrial application requirements of high-pressure hydrogen transmission pipelines, and has a good prospect for industrial promotion.

[0008] According to one aspect of the present application, a method for preparing a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline is provided, the method comprising the following steps: S1. Degreasing, cleaning and polishing of titanium alloy pipes; S2, first using PVD method to deposit a Ni layer on the surface of the titanium alloy, and then using chemical electroplating method to deposit a NiP-metal oxide composite coating on the surface; S3, taking Ni as the matrix, adding graphene oxide and sodium carboxymethyl cellulose solution to prepare a paste powder, and then applying the paste powder and performing laser cladding treatment; S4, sequentially preparing a Ni-La2O3 layer, a Si3N4-CeO2 layer and a Re2O7-Al2O3 layer by magnetron co-sputtering treatment, and finally completing the preparation of the hydrogen barrier coating for the high-pressure hydrogen transmission titanium alloy pipeline after heat preservation treatment; In the step S2, the metal oxide in the NiP-metal oxide composite coating is selected from one or more of Al2O3 nanoparticles, ZrO2 nanoparticles, Y2O3 nanoparticles, Cr2O3 nanoparticles, La2O3 nanoparticles, and CeO2 nanoparticles.

[0009] Optionally, the metal oxide in step S2 is a combination of Al2O3 nanoparticles and CeO2 nanoparticles.

[0010] Optionally, the graphene oxide in step S3 is graphene oxide that has been partially reduced by a reducing agent; The treatment method comprises the following steps: ultrasonically dispersing graphene oxide in DMF solvent, adding concentrated ammonia water as a promoter, and finally adding vitamin C to adjust the pH and carry out a reduction reaction, and then washing with pure water and drying under vacuum to obtain the graphene oxide treated with partial reduction by the reducing agent.

[0011] Optionally, the carbon-oxygen ratio of the reduced graphene oxide is (12~18):1.

[0012] Optionally, the sheet thickness of the graphene oxide that has not been partially reduced by the reducing agent is less than 1.0 nm, and the particle size D 50 The surface area is 250~300nm and the specific surface area is 300~350m 2 / g. Selecting the graphene oxide with the above-mentioned specific sheet thickness, particle size and specific surface area as the raw material can not only achieve a good hydrogen barrier effect, but also improve the dispersion effect of the graphene oxide, reduce the agglomeration of the graphene oxide, and extend the hydrogen permeation path, thereby reducing the hydrogen permeability of the Ni-graphene oxide layer.

[0013] Optionally, the preprocessing step S1 specifically includes: S1.1) Degreasing treatment: After washing the titanium alloy tube body with water, use acetone to degreasing it; S1.2) Polishing treatment: immerse the degreased tube body in a polishing treatment solution including pure nitric acid, pure hydrofluoric acid and pure sulfuric acid for polishing treatment; S1.3) Activation treatment: The polished tube body is placed in an activation treatment solution including NH4HF2, oxalic acid and pure sulfuric acid for activation treatment; S1.4) Corrosion inhibition treatment: The pipes to be used are temporarily stored in a corrosion inhibition solution including ethanol and NH4HF2.

[0014] Optionally, the step S1 specifically includes: S1.1) Degreasing treatment: After washing the titanium alloy tube body with water, use acetone to degreasing it; S1.2) Polishing: The degreased tube body is immersed in a polishing solution for polishing. The polishing solution includes pure nitric acid, pure hydrofluoric acid and pure sulfuric acid in a volume ratio of 2:1:1, wherein the mass fraction of pure nitric acid is 66%, the mass fraction of pure hydrofluoric acid is 40%, and the mass fraction of pure sulfuric acid is 98%; S1.3) Activation treatment: The polished tube body is placed in an activation treatment solution for activation treatment. The activation treatment solution includes: 5g / L NH4HF2, 20g / L oxalic acid and 50ml / L pure sulfuric acid, wherein the mass fraction of pure sulfuric acid is 98%; S1.4) Corrosion inhibition treatment: The pipe to be used is placed in a corrosion inhibition preservation solution, which includes: 1000L ethanol and 10g NH4HF2.

[0015] Optionally, the step S2 specifically includes: S2.1) Cleaning treatment: ultrasonically clean the tube in anhydrous ethanol; S2.2) Deposition of Ni layer: After ultrasonic cleaning and drying, the tube body is placed in a PVD coating furnace, evacuated and filled with Ar gas, and the temperature is raised to 300±50℃ to raise the pressure in the furnace to 5±1Pa. After the Ni arc target power supply is turned on for 120±30min, the Ni buffer layer is deposited on the substrate surface; S2.3) preparing chemical plating solution: weighing metal oxide nanoparticles and SDS, dispersing them in deionized water, and subjecting them to ultrasonic dispersion treatment to obtain chemical plating solution A; weighing NiSO4, NaH2PO2, C6H5Na3O7, H3BO3, and SDS, stirring and dispersing them, and obtaining chemical plating solution B; mixing chemical plating solution A and chemical plating solution B, and subjecting them to ultrasonic dispersion treatment to obtain chemical plating solution; S2.4) Chemical electroplating treatment: The tube body after ultrasonic cleaning and drying is placed in the prepared chemical electroplating solution, and after chemical plating bath at room temperature for 240±30 minutes, the preparation of NiP-metal oxide composite coating is completed.

[0016] Optionally, the step S2 specifically includes: S2.1) Cleaning treatment: The tube body is ultrasonically cleaned in anhydrous ethanol at an ultrasonic frequency of 20kHz and a power of 100W; S2.2) Deposition of Ni layer: After ultrasonic cleaning and drying, the tube body is placed in a PVD coating furnace and vacuumed to 1.0*10 -3After 120 min of deposition, the Ni buffer layer was deposited on the substrate surface. S2.3) Prepare chemical plating solution: weigh 5g metal oxide nanoparticles and 1g SDS and disperse them in 1L deionized water. After ultrasonic dispersion treatment, obtain chemical plating solution A. Chemical plating solution B includes: 60g / L NiSO4, 10g / L NaH2PO2, 60g / L C6H5Na3O7, 20g / L H3BO3 and 0.5g / L SDS. Mix chemical plating solution A and chemical plating solution B and ultrasonically treat for 30min to obtain chemical plating solution. S2.4) Chemical electroplating treatment: The tube body after ultrasonic cleaning and drying is placed in the prepared chemical electroplating solution, and after chemical plating bath at room temperature for 240 minutes, the preparation of NiP-metal oxide composite coating is completed.

[0017] Optionally, the step S3 specifically includes: S3.1) preparing a paste powder: mixing Ni powder and graphene oxide, ball milling, adding sodium carboxymethyl cellulose solution and stirring to obtain a paste powder; S3.2) Applying paste powder: After ultrasonic cleaning and drying the tube body, evenly apply the paste powder on the inner surface of the tube body and then heat and pre-bake; S3.3) Laser cladding treatment: Under argon protection, use laser cladding equipment to perform laser cladding treatment on the paste powder coating.

[0018] Optionally, the step S3 specifically includes: S3.1) preparing a paste powder: mixing Ni powder and graphene oxide in a mass ratio of 10:1 to obtain a powder, ball-milling the powder at a speed of 200 rpm for 240 min, adding 5 wt % sodium carboxymethyl cellulose solution and stirring to obtain a paste powder, wherein the mass ratio of the sodium carboxymethyl cellulose solution to the powder is 1:3; S3.2) Applying paste powder: After ultrasonic cleaning and drying the tube body, evenly apply the paste powder on the inner surface of the tube body with a coating thickness of 0.5 mm, and then bake at 200°C for 60 minutes; S3.3) Laser cladding treatment: Under argon protection, the paste powder coating is laser clad using laser cladding equipment with a laser power of 2.0 kW, a spot diameter of 5 mm, and a scanning speed of 3 mm / s; Optionally, the step S4 specifically includes: S4.1) Preparation of Ni-La2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5±0.1Pa, the Ni target sputtering power was 150±50W, the La2O3 target sputtering power was 250±50W, and the two targets were sputtered for deposition for 30±10min at the same time; S4.2) Preparation of Si3N4-CeO2 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5±0.1Pa, the Si3N4 target sputtering power was 200±50W, the CeO2 target sputtering power was 250±50W, and the two targets were sputtered for 60±20min at the same time; S4.3) Preparation of Re2O7-Al2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5±0.1Pa, the sputtering power of Al2O3 target was 100~150W, the sputtering power of Re2O7 target was 250±50W, and the two targets were sputtered and deposited for 180±30min at the same time; S4.4) Heat insulation treatment: keep the pipe in an Ar gas atmosphere at 500±50°C for 240±60 minutes to complete the preparation of the hydrogen barrier coating for the high-pressure hydrogen transmission titanium alloy pipeline.

[0019] Optionally, the step S3 specifically includes: S4.1) Preparation of Ni-La2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Ni target sputtering power was 150 W, the La2O3 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered simultaneously for 30 min; S4.2) Preparation of Si3N4-CeO2 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Si3N4 target sputtering power was 200 W, the CeO2 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 60 min at the same time; S4.3) Preparation of Re2O7-Al2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the sputtering power of Al2O3 target was 100 W, the sputtering power of Re2O7 target was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 180 min at the same time; S4.4) Heat insulation treatment: The pipe is kept in an Ar gas atmosphere at 500°C for 240 minutes to complete the preparation of the hydrogen barrier coating for the high-pressure hydrogen transmission titanium alloy pipeline.

[0020] According to another aspect of the present application, a titanium alloy high-pressure hydrogen transmission pipe is provided, which contains a hydrogen barrier coating prepared by any of the above-mentioned methods for preparing a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline.

[0021] The beneficial effects of this application are: 1. According to the hydrogen barrier coating for high-pressure hydrogen transmission titanium alloy pipeline and its preparation method of the present application, for the high-pressure hydrogen transmission pipeline with titanium alloy as the substrate, a Ni buffer layer, a NiP-metal oxide composite coating, a Ni-graphene oxide layer and an oxide ceramic layer are sequentially arranged from the inside to the outside. The Ni-graphene oxide layer can reduce the porosity and improve the hydrogen barrier performance of the coating. At the same time, the oxide ceramic layer with low hydrogen permeability coefficient and the NiP-metal oxide composite coating are selected as the hydrogen barrier layer, which can greatly improve the hydrogen barrier efficiency of the coating and play a role in sealing the pores. The pure Ni buffer layer can not only play a buffering role to improve the bonding strength between the coating and the titanium alloy substrate, but also reduce the porosity to further improve the hydrogen barrier performance.

[0022] 2. The hydrogen barrier coating for high-pressure hydrogen transmission titanium alloy pipeline and its preparation method according to the present application has a short preparation cycle and good construction performance on the inner wall of the high-pressure hydrogen transmission titanium alloy pipeline, which can effectively extend the service life of the high-pressure hydrogen transmission titanium alloy pipeline, thereby improving the safety of the high-pressure hydrogen transmission titanium alloy pipeline.

[0023] 3. The hydrogen barrier coating for high-pressure hydrogen transmission titanium alloy pipeline and its preparation method according to the present application are prepared by combining the currently mature and widely industrialized chemical plating, coating laser cladding treatment and magnetron co-sputtering treatment technology to prepare the composite hydrogen barrier coating, which has the advantages of low cost, convenient mass production, safety, environmental protection and no pollution.

[0024] 4. The hydrogen barrier coating for high-pressure hydrogen transmission titanium alloy pipeline and its preparation method according to the present application has high bonding strength and excellent hydrogen permeation resistance, which can effectively solve the problem that the current organic or inorganic hydrogen barrier coating cannot provide long-term protection or has poor hydrogen permeation resistance, and can fully meet the industrial application requirements of high-pressure hydrogen transmission pipelines, and has good prospects for industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings: Figure 1 This is a schematic diagram of the composite structure of the hydrogen barrier coating for the high-pressure hydrogen transmission titanium alloy pipeline involved in the embodiment of the present application; Figure 2 This is a flow chart for preparing the hydrogen barrier coating for the high-pressure hydrogen transmission titanium alloy pipeline involved in the embodiment of the present application. DETAILED DESCRIPTION

[0026] The present application is described in detail below in conjunction with examples, but the present application is not limited to these examples. Unless otherwise specified, the raw materials and catalysts in the examples of the present application are purchased through commercial channels.

[0027] like Figure 2 Shown is a flow chart for preparing a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline provided by the present application. The reagents or raw materials used in this application can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in this application are used in accordance with the conventional methods in the art or in accordance with the product instructions. In addition, any methods and materials similar or equivalent to those described herein can be applied to the method of this application. The preferred implementation methods and materials described in this patent are for demonstration purposes only. Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art.

[0028] It should be noted that the present application mainly aims at treating the inner wall of the hydrogen transmission pipeline of the titanium alloy pipe to achieve hydrogen penetration resistance and reduce the damage of high-pressure hydrogen to the titanium alloy pipe matrix. The present application does not limit or care about the structure of the outer wall. For example, the structure of the coating on the outer wall can be adjusted or selected according to needs or the characteristics of the processing technology. If necessary, an additional seawater corrosion-resistant coating can be designed for the outer layer according to seawater conditions. The existing technology of the coating process related to seawater corrosion resistance is relatively mature, so technical personnel in this field can design or make appropriate adjustments as needed.

[0029] The present application relates to the test of the bonding strength and hydrogen permeation resistance of the hydrogen barrier composite coating, wherein the bonding strength is specifically tested according to GB / T 30707-2014 "Fine Ceramic Coating Bonding Test Method Scratch Method". The coating sample is fixed on the sample table of the scratch tester, and the indenter is placed on the surface of the film. During the test, the indenter moves along the scratch direction as the load increases, wherein the maximum load is 100N, the loading rate is 100N / min, the scratch length is 5mm, the instrument is started to start the scratch test, and the load and acoustic signal are recorded at the same time. The bonding strength between the coating and the substrate is determined by the measurement method of acoustic emission; wherein the hydrogen permeation resistance test is specifically based on ASTM G 148-2011 "Standard Specification for Evaluating Hydrogen Absorption, Permeation and Transport in Metals by Electrochemical Technology", and a gas-driven permeation device is used to test the hydrogen permeation resistance, and a hydrogen permeation test is carried out under the conditions of simulating the high-pressure hydrogen transmission under the seabed at a pressure of 75kPa and a temperature of 5°C, and the hydrogen permeability reduction factor PRF is calculated.

[0030] The present application scheme is described below through specific embodiments.

[0031] Example 1 1) Pretreatment of titanium alloy pipes 1.1 Degreasing treatment: After washing the titanium alloy tube body with water, use acetone to degreasing it; 1.2 Polishing: Immerse the degreased tube body in a polishing solution for polishing. The polishing solution includes pure nitric acid, pure hydrofluoric acid and pure sulfuric acid in a volume ratio of 2:1:1, wherein the mass fraction of pure nitric acid is 66%, the mass fraction of pure hydrofluoric acid is 40%, and the mass fraction of pure sulfuric acid is 98%; 1.3 Activation treatment: Place the polished tube body in an activation treatment solution for activation treatment. The activation treatment solution includes: 5g / L NH4HF2, 20g / L oxalic acid and 50ml / L pure sulfuric acid, wherein the mass fraction of pure sulfuric acid is 98%; 1.4 Corrosion inhibition treatment: The pipes to be used are placed in a corrosion inhibition preservation solution, which includes: 1000L ethanol and 10g NH4HF2.

[0032] 2) Preparation of Ni buffer layer and NiP-metal oxide composite coating 2.1 Cleaning: The tube body is ultrasonically cleaned in anhydrous ethanol with an ultrasonic frequency of 20kHz and a power of 100W; 2.2 Deposition of Ni layer: After ultrasonic cleaning and drying, place the tube into the PVD coating furnace and evacuate to 1.0*10 -3 After 120 min of deposition, the Ni buffer layer was deposited on the substrate surface. 2.3 Prepare chemical plating solution: Weigh 5g metal oxide nanoparticles (metal oxide nanoparticles include 3g Al2O3 and 2g CeO2, the particle size of Al2O3 and CeO2 nanoparticles is D 50 50nm and 65nm respectively) and 1g SDS are dispersed in 1L deionized water, and solution A is obtained after ultrasonic dispersion treatment. Solution B includes: 60g / L NiSO4, 10g / L NaH2PO2, 60g / L C6H5Na3O7, 20g / L H3BO3 and 0.5g / L SDS. Solution A and solution B are mixed and ultrasonically treated for 30min to obtain a chemical plating solution; 2.4 Chemical electroplating treatment: the tube body after ultrasonic cleaning and drying is placed in the prepared chemical electroplating solution, and after chemical plating bath at room temperature for 240 minutes, the preparation of NiP-metal oxide composite coating is completed; 3) Preparation of Ni-graphene oxide layer 3.1 Preparation of paste powder: Ni powder, graphene oxide (sheet thickness less than 1.0nm, particle size D 50The surface area is 280 nm and the specific surface area is 320 m 2 / g, the graphene oxide is partially reduced, specifically, the graphene oxide is ultrasonically dispersed in a DMF solvent, concentrated ammonia is added as a promoter, and finally vitamin C is added to adjust the pH to 7, and then a reduction reaction is carried out at 60°C, and the partially reduced graphene oxide is obtained after washing with pure water and drying under vacuum, and the carbon-oxygen ratio of the partially reduced graphene oxide is 18:1) and mixed in a mass ratio of 10:1 to obtain a powder, and the powder is ball-milled at a speed of 200 rpm for 240 minutes, and then a 5wt% sodium carboxymethyl cellulose solution is added and stirred to obtain a paste powder, wherein the mass ratio of the sodium carboxymethyl cellulose solution to the powder is 1:3; 3.2 Coating the paste powder: After ultrasonic cleaning and drying the tube body, evenly coat the paste powder on the inner surface of the tube body with a coating thickness of 0.5 mm, and then bake at 200°C for 60 minutes; 3.3 Laser cladding treatment: Under argon protection, the paste powder coating was laser clad using laser cladding equipment with a laser power of 2.0 kW, a spot diameter of 5 mm, and a scanning speed of 3 mm / s; 4) Preparation of oxide ceramic layer 4.1 Preparation of Ni-La2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Ni target sputtering power was 150 W, the La2O3 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 30 min at the same time; 4.2 Preparation of Si3N4-CeO2 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Si3N4 target sputtering power was 200 W, the CeO2 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 60 min at the same time; 4.3 Preparation of Re2O7-Al2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the sputtering power of Al2O3 target was 100 W, the sputtering power of Re2O7 target was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 180 min at the same time; 4.4 Heat preservation treatment: The pipe is kept in an Ar gas atmosphere at 500°C for 240 minutes to complete the treatment.

[0033] The bonding strength of the hydrogen barrier composite coating was detected to be 82N, and the permeability reduction factor PRF was 1152.

[0034] Example 2 1) Pretreatment of titanium alloy pipes 1.1 Degreasing treatment: After washing the titanium alloy tube body with water, use acetone to degreasing it; 1.2 Polishing: Immerse the degreased tube body in a polishing solution for polishing. The polishing solution includes pure nitric acid, pure hydrofluoric acid and pure sulfuric acid in a volume ratio of 2:1:1, wherein the mass fraction of pure nitric acid is 66%, the mass fraction of pure hydrofluoric acid is 40%, and the mass fraction of pure sulfuric acid is 98%; 1.3 Activation treatment: Place the polished tube body in an activation treatment solution for activation treatment. The activation treatment solution includes: 5g / L NH4HF2, 20g / L oxalic acid and 50ml / L pure sulfuric acid, wherein the mass fraction of pure sulfuric acid is 98%; 1.4 Corrosion inhibition treatment: The pipes to be used are placed in a corrosion inhibition preservation solution, which includes: 1000L ethanol and 10g NH4HF2.

[0035] 2) Preparation of Ni buffer layer and NiP-metal oxide composite coating 2.1 Cleaning: The tube body is ultrasonically cleaned in anhydrous ethanol with an ultrasonic frequency of 20kHz and a power of 100W; 2.2 Deposition of Ni layer: After ultrasonic cleaning and drying, place the tube into the PVD coating furnace and evacuate to 1.0*10 -3 After 120 min of deposition, the Ni buffer layer was deposited on the substrate surface. 2.3 Prepare chemical plating solution: Weigh 5g metal oxide nanoparticles (metal oxide nanoparticles include 3g Al2O3 and 2g CeO2, the particle size of Al2O3 and CeO2 nanoparticles is D 50 50nm and 62nm respectively) and 1g SDS are dispersed in 1L deionized water, and solution A is obtained after ultrasonic dispersion treatment. Solution B includes: 60g / L NiSO4, 10g / L NaH2PO2, 60g / L C6H5Na3O7, 20g / L H3BO3 and 0.5g / L SDS. Solution A and solution B are mixed and ultrasonically treated for 30min to obtain a chemical plating solution; 2.4 Chemical electroplating treatment: the tube body after ultrasonic cleaning and drying is placed in the prepared chemical electroplating solution, and after chemical plating bath at room temperature for 240 minutes, the preparation of NiP-metal oxide composite coating is completed; 3) Preparation of Ni-graphene oxide layer 3.1 Preparation of paste powder: Ni powder, graphene oxide (sheet thickness less than 1.0nm, particle size D 50 The surface area is 280 nm and the specific surface area is 320 m 2 / g, the graphene oxide is partially reduced, specifically, the graphene oxide is ultrasonically dispersed in a DMF solvent, concentrated ammonia is added as a promoter, and finally vitamin C is added to adjust the pH to 7, and then a reduction reaction is carried out at 60°C, and the partially reduced graphene oxide is obtained after washing with pure water and drying under vacuum, and the carbon-oxygen ratio of the partially reduced graphene oxide is 12:1) and mixed in a mass ratio of 10:1 to obtain a powder, and the powder is ball-milled at a speed of 200 rpm for 240 minutes, and then a 5wt% sodium carboxymethyl cellulose solution is added and stirred to obtain a paste powder, wherein the mass ratio of the sodium carboxymethyl cellulose solution to the powder is 1:3; 3.2 Coating the paste powder: After ultrasonic cleaning and drying the tube body, evenly coat the paste powder on the inner surface of the tube body with a coating thickness of 0.5 mm, and then bake at 200°C for 60 minutes; 3.3 Laser cladding treatment: Under argon protection, the paste powder coating was laser clad using laser cladding equipment with a laser power of 2.0 kW, a spot diameter of 5 mm, and a scanning speed of 3 mm / s; 4) Preparation of oxide ceramic layer 4.1 Preparation of Ni-La2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Ni target sputtering power was 150 W, the La2O3 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 30 min at the same time; 4.2 Preparation of Si3N4-CeO2 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Si3N4 target sputtering power was 200 W, the CeO2 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 60 min at the same time; 4.3 Preparation of Re2O7-Al2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the sputtering power of Al2O3 target was 100 W, the sputtering power of Re2O7 target was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 180 min at the same time; 4.4 Heat preservation treatment: The pipe is kept in an Ar gas atmosphere at 500°C for 240 minutes to complete the treatment.

[0036] The bonding strength of the hydrogen barrier composite coating was detected to be 80N, and the permeability reduction factor PRF was 1127.

[0037] Example 3 1) Pretreatment of titanium alloy pipes 1.1 Degreasing treatment: After washing the titanium alloy tube body with water, use acetone to degreasing it; 1.2 Polishing: Immerse the degreased tube body in a polishing solution for polishing. The polishing solution includes pure nitric acid, pure hydrofluoric acid and pure sulfuric acid in a volume ratio of 2:1:1, wherein the mass fraction of pure nitric acid is 66%, the mass fraction of pure hydrofluoric acid is 40%, and the mass fraction of pure sulfuric acid is 98%; 1.3 Activation treatment: Place the polished tube body in an activation treatment solution for activation treatment. The activation treatment solution includes: 5g / L NH4HF2, 20g / L oxalic acid and 50ml / L pure sulfuric acid, wherein the mass fraction of pure sulfuric acid is 98%; 1.4 Corrosion inhibition treatment: The pipes to be used are placed in a corrosion inhibition preservation solution, which includes: 1000L ethanol and 10g NH4HF2.

[0038] 2) Preparation of Ni buffer layer and NiP-metal oxide composite coating 2.1 Cleaning: The tube body is ultrasonically cleaned in anhydrous ethanol with an ultrasonic frequency of 20kHz and a power of 100W; 2.2 Deposition of Ni layer: After ultrasonic cleaning and drying, place the tube into the PVD coating furnace and evacuate to 1.0*10 -3 After 120 min of deposition, the Ni buffer layer was deposited on the substrate surface. 2.3 Prepare chemical plating solution: Weigh 5g metal oxide nanoparticles (metal oxide nanoparticles include 3g Al2O3 and 2g ZrO2, the particle size of Al2O3 and ZrO2 nanoparticles is D 50 50nm) and 1g SDS are dispersed in 1L deionized water, and a solution A is obtained after ultrasonic dispersion treatment. The solution B includes: 60g / L NiSO4, 10g / L NaH2PO2, 60g / L C6H5Na3O7, 20g / LH3BO3 and 0.5g / L SDS. The solution A and the solution B are mixed and ultrasonically treated for 30min to obtain a chemical plating solution; 2.4 Chemical electroplating treatment: the tube body after ultrasonic cleaning and drying is placed in the prepared chemical electroplating solution, and after chemical plating bath at room temperature for 240 minutes, the preparation of NiP-metal oxide composite coating is completed; 3) Preparation of Ni-graphene oxide layer 3.1 Preparation of paste powder: Ni powder, graphene oxide (sheet thickness less than 1.0nm, particle size D 50 The surface area is 250 nm and the specific surface area is 300 m 2 / g, carbon-oxygen ratio is 3:1) in a mass ratio of 10:1 to obtain powder, the powder is ball-milled at a speed of 200 rpm for 240 min, and then a 5wt% sodium carboxymethyl cellulose solution is added and stirred to obtain a paste powder, wherein the mass ratio of the sodium carboxymethyl cellulose solution to the powder is 1:3; 3.2 Coating the paste powder: After ultrasonic cleaning and drying the tube body, evenly coat the paste powder on the inner surface of the tube body with a coating thickness of 0.5 mm, and then bake at 200°C for 60 minutes; 3.3 Laser cladding treatment: Under argon protection, the paste powder coating was laser clad using laser cladding equipment with a laser power of 2.0 kW, a spot diameter of 5 mm, and a scanning speed of 3 mm / s; 4) Preparation of oxide ceramic layer 4.1 Preparation of Ni-La2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Ni target sputtering power was 150 W, the La2O3 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 30 min at the same time; 4.2 Preparation of Si3N4-CeO2 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Si3N4 target sputtering power was 200 W, the CeO2 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 60 min at the same time; 4.3 Preparation of Re2O7-Al2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the sputtering power of Al2O3 target was 100 W, the sputtering power of Re2O7 target was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 180 min at the same time; 4.4 Heat preservation treatment: The pipe is kept in an Ar gas atmosphere at 500°C for 240 minutes to complete the treatment.

[0039] The bonding strength of the hydrogen barrier composite coating was detected to be 81N, and the permeability reduction factor PRF was 814.

[0040] Example 4 1) Pretreatment of titanium alloy pipes 1.1 Degreasing treatment: After washing the titanium alloy tube body with water, use acetone to degreasing it; 1.2 Polishing: Immerse the degreased tube body in a polishing solution for polishing. The polishing solution includes pure nitric acid, pure hydrofluoric acid and pure sulfuric acid in a volume ratio of 2:1:1, wherein the mass fraction of pure nitric acid is 66%, the mass fraction of pure hydrofluoric acid is 40%, and the mass fraction of pure sulfuric acid is 98%; 1.3 Activation treatment: Place the polished tube body in an activation treatment solution for activation treatment. The activation treatment solution includes: 5g / L NH4HF2, 20g / L oxalic acid and 50ml / L pure sulfuric acid, wherein the mass fraction of pure sulfuric acid is 98%; 1.4 Corrosion inhibition treatment: The pipes to be used are placed in a corrosion inhibition preservation solution, which includes: 1000L ethanol and 10g NH4HF2.

[0041] 2) Preparation of Ni buffer layer and NiP-metal oxide composite coating 2.1 Cleaning: The tube body is ultrasonically cleaned in anhydrous ethanol with an ultrasonic frequency of 20kHz and a power of 100W; 2.2 Deposition of Ni layer: After ultrasonic cleaning and drying, place the tube into the PVD coating furnace and evacuate to 1.0*10 -3 After 120 min of deposition, the Ni buffer layer was deposited on the substrate surface. 2.3 Prepare chemical plating solution: weigh 5g metal oxide nanoparticles (metal oxide nanoparticles include 3g Al2O3 and 2g Y2O3, the particle size of Al2O3 and Y2O3 nanoparticles is D 50 50nm, 64nm respectively) and 1g SDS are dispersed in 1L deionized water, and liquid A is obtained after ultrasonic dispersion treatment. Liquid B includes: 60g / L NiSO4, 10g / L NaH2PO2, 60g / L C6H5Na3O7, 20g / L H3BO3 and 0.5g / L SDS. Liquid A and liquid B are mixed and ultrasonically treated for 30min to obtain a chemical plating solution; 2.4 Chemical electroplating treatment: the tube body after ultrasonic cleaning and drying is placed in the prepared chemical electroplating solution, and after chemical plating bath at room temperature for 240 minutes, the preparation of NiP-metal oxide composite coating is completed; 3) Preparation of Ni-graphene oxide layer 3.1 Preparation of paste powder: Ni powder, graphene oxide (sheet thickness less than 1.0nm, particle size D 50 The surface area is 350m 2 / g, the graphene oxide has not been partially reduced, and the carbon-oxygen ratio is 3:1) is mixed in a mass ratio of 10:1 to obtain a powder, the powder is ball-milled at a speed of 200 rpm for 240 minutes, and a 5wt% sodium carboxymethyl cellulose solution is added and stirred to obtain a paste powder, wherein the mass ratio of the sodium carboxymethyl cellulose solution to the powder is 1:3; 3.2 Coating the paste powder: After ultrasonic cleaning and drying the tube body, evenly coat the paste powder on the inner surface of the tube body with a coating thickness of 0.5 mm, and then bake at 200°C for 60 minutes; 3.3 Laser cladding treatment: Under argon protection, the paste powder coating was laser clad using laser cladding equipment with a laser power of 2.0 kW, a spot diameter of 5 mm, and a scanning speed of 3 mm / s; 4) Preparation of oxide ceramic layer 4.1 Preparation of Ni-La2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Ni target sputtering power was 150 W, the La2O3 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 30 min at the same time; 4.2 Preparation of Si3N4-CeO2 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Si3N4 target sputtering power was 200 W, the CeO2 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 60 min at the same time; 4.3 Preparation of Re2O7-Al2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the sputtering power of Al2O3 target was 100 W, the sputtering power of Re2O7 target was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 180 min at the same time; 4.4 Heat preservation treatment: The pipe is kept in an Ar gas atmosphere at 500°C for 240 minutes to complete the treatment.

[0042] The bonding strength of the hydrogen barrier composite coating was detected to be 83N, and the permeability reduction factor PRF was 883.

[0043] Example 5 1) Pretreatment of titanium alloy pipes 1.1 Degreasing treatment: After washing the titanium alloy tube body with water, use acetone to degreasing it; 1.2 Polishing: Immerse the degreased tube body in a polishing solution for polishing. The polishing solution includes pure nitric acid, pure hydrofluoric acid and pure sulfuric acid in a volume ratio of 2:1:1, wherein the mass fraction of pure nitric acid is 66%, the mass fraction of pure hydrofluoric acid is 40%, and the mass fraction of pure sulfuric acid is 98%; 1.3 Activation treatment: Place the polished tube body in an activation treatment solution for activation treatment. The activation treatment solution includes: 5g / L NH4HF2, 20g / L oxalic acid and 50ml / L pure sulfuric acid, wherein the mass fraction of pure sulfuric acid is 98%; 1.4 Corrosion inhibition treatment: The pipes to be used are placed in a corrosion inhibition preservation solution, which includes: 1000L ethanol and 10g NH4HF2.

[0044] 2) Preparation of Ni buffer layer and NiP-metal oxide composite coating 2.1 Cleaning: The tube body is ultrasonically cleaned in anhydrous ethanol with an ultrasonic frequency of 20kHz and a power of 100W; 2.2 Deposition of Ni layer: After ultrasonic cleaning and drying, place the tube into the PVD coating furnace and evacuate to 1.0*10 -3 After 120 min of deposition, the Ni buffer layer was deposited on the substrate surface. 2.3 Preparation of chemical plating solution: Weigh 5g of metal oxide nanoparticles (the metal oxide nanoparticles include 3g Al2O3 and 2g Cr2O3, the particle size of Al2O3 and Cr2O3 nanoparticles is D 50 50nm, 68nm respectively) and 1g SDS are dispersed in 1L deionized water, and liquid A is obtained after ultrasonic dispersion treatment. Liquid B includes: 60g / L NiSO4, 10g / L NaH2PO2, 60g / L C6H5Na3O7, 20g / L H3BO3 and 0.5g / L SDS. Liquid A and liquid B are mixed and ultrasonically treated for 30min to obtain a chemical plating solution; 2.4 Chemical electroplating treatment: the tube body after ultrasonic cleaning and drying is placed in the prepared chemical electroplating solution, and after chemical plating bath at room temperature for 240 minutes, the preparation of NiP-metal oxide composite coating is completed; 3) Preparation of Ni-graphene oxide layer 3.1 Preparation of paste powder: Ni powder, graphene oxide (sheet thickness less than 1.0nm, particle size D 50 The surface area is 280 nm and the specific surface area is 320 m 2 / g, the graphene oxide is partially reduced, specifically, the graphene oxide is ultrasonically dispersed in a DMF solvent, concentrated ammonia is added as a promoter, and finally vitamin C is added to adjust the pH to 7, and then a reduction reaction is carried out at 60°C, and the partially reduced graphene oxide is obtained after washing with pure water and drying under vacuum, and the carbon-oxygen ratio of the partially reduced graphene oxide is 18:1) and mixed in a mass ratio of 10:1 to obtain a powder, and the powder is ball-milled at a speed of 200 rpm for 240 minutes, and then a 5wt% sodium carboxymethyl cellulose solution is added and stirred to obtain a paste powder, wherein the mass ratio of the sodium carboxymethyl cellulose solution to the powder is 1:3; 3.2 Coating the paste powder: After ultrasonic cleaning and drying the tube body, evenly coat the paste powder on the inner surface of the tube body with a coating thickness of 0.5 mm, and then bake at 200°C for 60 minutes; 3.3 Laser cladding treatment: Under argon protection, the paste powder coating was laser clad using laser cladding equipment with a laser power of 2.0 kW, a spot diameter of 5 mm, and a scanning speed of 3 mm / s; 4) Preparation of oxide ceramic layer 4.1 Preparation of Ni-La2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Ni target sputtering power was 150 W, the La2O3 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 30 min at the same time; 4.2 Preparation of Si3N4-CeO2 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Si3N4 target sputtering power was 200 W, the CeO2 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 60 min at the same time; 4.3 Preparation of Re2O7-Al2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the sputtering power of Al2O3 target was 100 W, the sputtering power of Re2O7 target was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 180 min at the same time; 4.4 Heat preservation treatment: The pipe is kept in an Ar gas atmosphere at 500°C for 240 minutes to complete the treatment.

[0045] The bonding strength of the hydrogen barrier composite coating was detected to be 78N, and the permeability reduction factor PRF was 939.

[0046] Example 6 1) Pretreatment of titanium alloy pipes 1.1 Degreasing treatment: After washing the titanium alloy tube body with water, use acetone to degreasing it; 1.2 Polishing: Immerse the degreased tube body in a polishing solution for polishing. The polishing solution includes pure nitric acid, pure hydrofluoric acid and pure sulfuric acid in a volume ratio of 2:1:1, wherein the mass fraction of pure nitric acid is 66%, the mass fraction of pure hydrofluoric acid is 40%, and the mass fraction of pure sulfuric acid is 98%; 1.3 Activation treatment: Place the polished tube body in an activation treatment solution for activation treatment. The activation treatment solution includes: 5g / L NH4HF2, 20g / L oxalic acid and 50ml / L pure sulfuric acid, wherein the mass fraction of pure sulfuric acid is 98%; 1.4 Corrosion inhibition treatment: The pipes to be used are placed in a corrosion inhibition preservation solution, which includes: 1000L ethanol and 10g NH4HF2.

[0047] 2) Preparation of Ni buffer layer and NiP-metal oxide composite coating 2.1 Cleaning: The tube body is ultrasonically cleaned in anhydrous ethanol with an ultrasonic frequency of 20kHz and a power of 100W; 2.2 Deposition of Ni layer: After ultrasonic cleaning and drying, place the tube into the PVD coating furnace and evacuate to 1.0*10 -3 After 120 min of deposition, the Ni buffer layer was deposited on the substrate surface. 2.3 Prepare chemical plating solution: Weigh 5g metal oxide nanoparticles (metal oxide nanoparticles include 3g Al2O3 and 2g CeO2, the particle size of Al2O3 and CeO2 nanoparticles is D 50 50nm and 65nm respectively) and 1g SDS are dispersed in 1L deionized water, and solution A is obtained after ultrasonic dispersion treatment. Solution B includes: 60g / L NiSO4, 10g / L NaH2PO2, 60g / L C6H5Na3O7, 20g / L H3BO3 and 0.5g / L SDS. Solution A and solution B are mixed and ultrasonically treated for 30min to obtain a chemical plating solution; 2.4 Chemical electroplating treatment: the tube body after ultrasonic cleaning and drying is placed in the prepared chemical electroplating solution, and after chemical plating bath at room temperature for 240 minutes, the preparation of NiP-metal oxide composite coating is completed; 3) Preparation of Ni-graphene oxide layer 3.1 Preparation of paste powder: Ni powder, graphene oxide (sheet thickness less than 1.0nm, particle size D 50 The surface area is 280 nm and the specific surface area is 320 m 2 / g, the graphene oxide is partially reduced, specifically, the graphene oxide is ultrasonically dispersed in a DMF solvent, concentrated ammonia is added as a promoter, and finally vitamin C is added to adjust the pH to 7, and then a reduction reaction is carried out at 60°C, and the partially reduced graphene oxide is obtained after washing with pure water and drying under vacuum, and the carbon-oxygen ratio of the partially reduced graphene oxide is 20:1) and mixed in a mass ratio of 10:1 to obtain a powder, and the powder is ball-milled at a speed of 200 rpm for 240 minutes, and then a 5wt% sodium carboxymethyl cellulose solution is added and stirred to obtain a paste powder, wherein the mass ratio of the sodium carboxymethyl cellulose solution to the powder is 1:3; 3.2 Coating the paste powder: After ultrasonic cleaning and drying the tube body, evenly coat the paste powder on the inner surface of the tube body with a coating thickness of 0.5 mm, and then bake at 200°C for 60 minutes; 3.3 Laser cladding treatment: Under argon protection, the paste powder coating was laser clad using laser cladding equipment with a laser power of 2.0 kW, a spot diameter of 5 mm, and a scanning speed of 3 mm / s; 4) Preparation of oxide ceramic layer 4.1 Preparation of Ni-La2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Ni target sputtering power was 150 W, the La2O3 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 30 min at the same time; 4.2 Preparation of Si3N4-CeO2 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Si3N4 target sputtering power was 200 W, the CeO2 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 60 min at the same time; 4.3 Preparation of Re2O7-Al2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the sputtering power of Al2O3 target was 100 W, the sputtering power of Re2O7 target was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 180 min at the same time; 4.4 Heat preservation treatment: The pipe is kept in an Ar gas atmosphere at 500°C for 240 minutes to complete the treatment.

[0048] The bonding strength of the hydrogen barrier composite coating was detected to be 82N, and the permeability reduction factor PRF was 718.

[0049] Comparative Example 1 1) Pretreatment of titanium alloy pipes 1.1 Degreasing treatment: After washing the titanium alloy tube body with water, use acetone to degreasing it; 1.2 Polishing: Immerse the degreased tube body in a polishing solution for polishing. The polishing solution includes pure nitric acid, pure hydrofluoric acid and pure sulfuric acid in a volume ratio of 2:1:1, wherein the mass fraction of pure nitric acid is 66%, the mass fraction of pure hydrofluoric acid is 40%, and the mass fraction of pure sulfuric acid is 98%; 1.3 Activation treatment: Place the polished tube body in an activation treatment solution for activation treatment. The activation treatment solution includes: 5g / L NH4HF2, 20g / L oxalic acid and 50ml / L pure sulfuric acid, wherein the mass fraction of pure sulfuric acid is 98%; 1.4 Corrosion inhibition treatment: The pipes to be used are placed in a corrosion inhibition preservation solution, which includes: 1000L ethanol and 10g NH4HF2.

[0050] 2) Preparation of NiP-metal oxide composite coating 2.1 Cleaning: The tube body is ultrasonically cleaned in anhydrous ethanol with an ultrasonic frequency of 20kHz and a power of 100W; 2.2 Preparation of chemical plating solution: Weigh 5g of metal oxide nanoparticles (the metal oxide nanoparticles include 3g Al2O3 and 2g CeO2, the particle size of Al2O3 and CeO2 nanoparticles is D 50 50nm and 65nm respectively) and 1g SDS are dispersed in 1L deionized water, and solution A is obtained after ultrasonic dispersion treatment. Solution B includes: 60g / L NiSO4, 10g / L NaH2PO2, 60g / L C6H5Na3O7, 20g / L H3BO3 and 0.5g / L SDS. Solution A and solution B are mixed and ultrasonically treated for 30min to obtain a chemical plating solution; 2.3 Chemical plating treatment: the tube body after ultrasonic cleaning and drying is placed in the prepared chemical plating solution, and after chemical plating bath at room temperature for 240 minutes, the preparation of NiP-metal oxide composite coating is completed; 3) Preparation of Ni-graphene oxide layer 3.1 Preparation of paste powder: Ni powder, graphene oxide (sheet thickness less than 1.0nm, particle size D 50 The surface area is 280 nm and the specific surface area is 320 m 2 / g, the graphene oxide is partially reduced, specifically, the graphene oxide is ultrasonically dispersed in a DMF solvent, concentrated ammonia is added as a promoter, and finally vitamin C is added to adjust the pH to 7, and then a reduction reaction is carried out at 60°C, and the partially reduced graphene oxide is obtained after washing with pure water and drying under vacuum, and the carbon-oxygen ratio of the partially reduced graphene oxide is 18:1) and mixed in a mass ratio of 10:1 to obtain a powder, and the powder is ball-milled at a speed of 200 rpm for 240 minutes, and then a 5wt% sodium carboxymethyl cellulose solution is added and stirred to obtain a paste powder, wherein the mass ratio of the sodium carboxymethyl cellulose solution to the powder is 1:3; 3.2 Coating the paste powder: After ultrasonic cleaning and drying the tube body, evenly coat the paste powder on the inner surface of the tube body with a coating thickness of 0.5 mm, and then bake at 200°C for 60 minutes; 3.3 Laser cladding treatment: Under argon protection, the paste powder coating was laser clad using laser cladding equipment with a laser power of 2.0 kW, a spot diameter of 5 mm, and a scanning speed of 3 mm / s; 4) Preparation of oxide ceramic layer 4.1 Preparation of Ni-La2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Ni target sputtering power was 150 W, the La2O3 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 30 min at the same time; 4.2 Preparation of Si3N4-CeO2 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Si3N4 target sputtering power was 200 W, the CeO2 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 60 min at the same time; 4.3 Preparation of Re2O7-Al2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the sputtering power of Al2O3 target was 100 W, the sputtering power of Re2O7 target was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 180 min at the same time; 4.4 Heat preservation treatment: The pipe is kept in an Ar gas atmosphere at 500°C for 240 minutes to complete the treatment.

[0051] The bonding strength of the hydrogen barrier composite coating was detected to be 64N, and the permeability reduction factor PRF was 1006.

[0052] Comparative Example 2 1) Pretreatment of titanium alloy pipes 1.1 Degreasing treatment: After washing the titanium alloy tube body with water, use acetone to degreasing it; 1.2 Polishing: Immerse the degreased tube body in a polishing solution for polishing. The polishing solution includes pure nitric acid, pure hydrofluoric acid and pure sulfuric acid in a volume ratio of 2:1:1, wherein the mass fraction of pure nitric acid is 66%, the mass fraction of pure hydrofluoric acid is 40%, and the mass fraction of pure sulfuric acid is 98%; 1.3 Activation treatment: Place the polished tube body in an activation treatment solution for activation treatment. The activation treatment solution includes: 5g / L NH4HF2, 20g / L oxalic acid and 50ml / L pure sulfuric acid, wherein the mass fraction of pure sulfuric acid is 98%; 1.4 Corrosion inhibition treatment: The pipes to be used are placed in a corrosion inhibition preservation solution, which includes: 1000L ethanol and 10g NH4HF2.

[0053] 2) Preparation of Ni buffer layer and NiP-metal oxide composite coating 2.1 Cleaning: The tube body is ultrasonically cleaned in anhydrous ethanol with an ultrasonic frequency of 20kHz and a power of 100W; 2.2 Deposition of Ni layer: After ultrasonic cleaning and drying, place the tube into the PVD coating furnace and evacuate to 1.0*10 -3 After 120 min of deposition, the Ni buffer layer was deposited on the substrate surface. 2.3 Prepare chemical plating solution: Weigh 5g metal oxide nanoparticles (metal oxide nanoparticles include 3g Al2O3 and 2g CeO2, the particle size of Al2O3 and CeO2 nanoparticles is D 50 50nm and 65nm respectively) and 1g SDS are dispersed in 1L deionized water, and solution A is obtained after ultrasonic dispersion treatment. Solution B includes: 60g / L NiSO4, 10g / L NaH2PO2, 60g / L C6H5Na3O7, 20g / L H3BO3 and 0.5g / L SDS. Solution A and solution B are mixed and ultrasonically treated for 30min to obtain a chemical plating solution; 2.4 Chemical electroplating treatment: the tube body after ultrasonic cleaning and drying is placed in the prepared chemical electroplating solution, and after chemical plating bath at room temperature for 240 minutes, the preparation of NiP-metal oxide composite coating is completed; 3) Preparation of Ni-graphene oxide layer 3.1 Preparation of paste powder: Ni powder, graphene oxide (sheet thickness less than 1.0nm, particle size D 50 The surface area is 280 nm and the specific surface area is 320 m 2 / g, the graphene oxide is partially reduced, specifically, the graphene oxide is ultrasonically dispersed in a DMF solvent, concentrated ammonia is added as a promoter, and finally vitamin C is added to adjust the pH to 7, and then a reduction reaction is carried out at 60°C, and the partially reduced graphene oxide is obtained after washing with pure water and drying under vacuum, and the carbon-oxygen ratio of the partially reduced graphene oxide is 18:1) and mixed in a mass ratio of 10:1 to obtain a powder, and the powder is ball-milled at a speed of 200 rpm for 240 minutes, and then a 5wt% sodium carboxymethyl cellulose solution is added and stirred to obtain a paste powder, wherein the mass ratio of the sodium carboxymethyl cellulose solution to the powder is 1:3; 3.2 Coating the paste powder: After ultrasonic cleaning and drying the tube body, evenly coat the paste powder on the inner surface of the tube body with a coating thickness of 0.5 mm, and then bake at 200°C for 60 minutes; 3.3 Laser cladding treatment: Under argon protection, the paste powder coating was laser clad using laser cladding equipment with a laser power of 2.0 kW, a spot diameter of 5 mm, and a scanning speed of 3 mm / s; 4) Preparation of oxide ceramic layer 4.1 Preparation of Ni-La2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Ni target sputtering power was 150 W, the La2O3 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 30 min at the same time; 4.2 Preparation of Si3N4-CeO2 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5 Pa, the Si3N4 target sputtering power was 200 W, the CeO2 target sputtering power was 250 W, the target-substrate distance was 100 mm, and the two targets were sputtered and deposited for 60 min at the same time; 4.3 Heat preservation treatment: The pipe is kept in an Ar gas atmosphere at 500°C for 240 minutes to complete the treatment.

[0054] The binding force of the hydrogen barrier composite coating was detected to be 81N, and the permeability reduction factor PRF was 852. The test also found that the hardness and surface scratch resistance of the composite coating were poor. When used for high-pressure hydrogen transmission, the coating was easily damaged and had a short service life.

[0055] The test results of the embodiments and comparative examples are summarized in Table 1 below.

[0056] Table 1 Test results of hydrogen barrier coatings of examples and comparative examples

[0057] like Figure 1 As shown, the hydrogen barrier coating provided by the present application is aimed at the high-pressure hydrogen transmission titanium alloy pipeline, and a Ni buffer layer, a NiP-metal oxide composite coating, a Ni-graphene oxide layer and an oxide ceramic layer are arranged from the inside to the outside. The oxide ceramic layer on the surface not only has excellent anti-penetration ability to high-pressure hydrogen, but also has good strength to meet the requirements of maintaining stability after high-pressure hydrogen impact, and can play a better barrier effect on hydrogen. The Ni-graphene oxide layer uses partially reduced graphene oxide with a carbon-oxygen ratio of 12 to 18:1, which can not only ensure the hydrogen barrier performance of the graphene oxide plane but also improve the dispersion uniformity of the graphene oxide plane in Ni, and can reduce the porosity and thus significantly improve the performance of hydrogen penetration resistance. In addition, a Ni buffer layer is arranged between the NiP-metal oxide composite coating and the titanium alloy substrate, which can not only improve the bonding force of the hydrogen barrier composite coating, but also the dense pure Ni layer formed by arc discharge deposition can also play a certain role in hydrogen penetration resistance. The hydrogen barrier composite coating provided by the present application can fully meet the industrial application requirements of high-pressure hydrogen transmission pipelines and has a good prospect for industrial promotion.

[0058] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline, characterized in that: The method comprises the following steps: S1. Degreasing, cleaning and polishing of titanium alloy pipes; S2, first using PVD method to deposit a Ni layer on the surface of the titanium alloy, and then using chemical electroplating method to deposit a NiP-metal oxide composite coating on the surface; S3, taking Ni as the matrix, adding graphene oxide and sodium carboxymethyl cellulose solution to prepare a paste powder, and then applying the paste powder and performing laser cladding treatment; S4, sequentially preparing a Ni-La2O3 layer, a Si3N4-CeO2 layer and a Re2O7-Al2O3 layer by magnetron co-sputtering treatment, and finally completing the preparation of the hydrogen barrier coating for the high-pressure hydrogen transmission titanium alloy pipeline after heat preservation treatment; In the step S2, the metal oxide in the NiP-metal oxide composite coating is selected from one or more of Al2O3 nanoparticles, ZrO2 nanoparticles, Y2O3 nanoparticles, Cr2O3 nanoparticles, La2O3 nanoparticles, and CeO2 nanoparticles.

2. The method for preparing a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline according to claim 1, characterized in that: The metal oxide in step S2 is a combination of Al2O3 nanoparticles and CeO2 nanoparticles.

3. The method for preparing a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline according to claim 1, characterized in that: The graphene oxide in step S3 is graphene oxide that has been partially reduced by a reducing agent; The treatment method comprises the following steps: ultrasonically dispersing graphene oxide in DMF solvent, adding concentrated ammonia water as a promoter, and finally adding vitamin C to adjust the pH and carry out a reduction reaction, and then washing with pure water and drying under vacuum to obtain the graphene oxide treated with partial reduction by the reducing agent.

4. The method for preparing a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline according to claim 3, characterized in that: The carbon-oxygen ratio of graphene oxide after reduction treatment is (12~18):

1.

5. The method for preparing a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline according to claim 3, characterized in that: The sheet thickness of graphene oxide that has not been partially reduced by a reducing agent is less than 1.0 nm, and the particle size D 50 The surface area is 250~300nm and the specific surface area is 300~350m 2 / g.

6. The method for preparing a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline according to claim 1, characterized in that: The preprocessing step S1 specifically includes: S1.1) Degreasing treatment: After washing the titanium alloy tube body with water, use acetone to degreasing it; S1.2) Polishing treatment: immerse the degreased tube body in a polishing treatment solution including pure nitric acid, pure hydrofluoric acid and pure sulfuric acid for polishing treatment; S1.3) Activation treatment: The polished tube body is placed in an activation treatment solution including NH4HF2, oxalic acid and pure sulfuric acid for activation treatment; S1.4) Corrosion inhibition treatment: The pipes to be used are temporarily stored in a corrosion inhibition solution including ethanol and NH4HF2.

7. The method for preparing a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline according to claim 1, characterized in that: The step S2 specifically includes: S2.1) Cleaning treatment: ultrasonically clean the tube in anhydrous ethanol; S2.2) Deposition of Ni layer: After ultrasonic cleaning and drying, the tube body is placed in a PVD coating furnace, evacuated and filled with Ar gas, and the temperature is raised to 300±50℃ to raise the pressure in the furnace to 5±1Pa. After the Ni arc target power supply is turned on for 120±30min, the Ni buffer layer is deposited on the substrate surface; S2.3) preparing chemical plating solution: weighing metal oxide nanoparticles and SDS, dispersing them in deionized water, and subjecting them to ultrasonic dispersion treatment to obtain chemical plating solution A; weighing NiSO4, NaH2PO2, C6H5Na3O7, H3BO3, and SDS, stirring and dispersing them, and obtaining chemical plating solution B; mixing chemical plating solution A and chemical plating solution B, and subjecting them to ultrasonic dispersion treatment to obtain chemical plating solution; S2.4) Chemical electroplating treatment: The tube body after ultrasonic cleaning and drying is placed in the prepared chemical electroplating solution, and after chemical plating bath at room temperature for 240±30 minutes, the preparation of NiP-metal oxide composite coating is completed.

8. The method for preparing a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline according to claim 1, characterized in that: The step S3 specifically includes: S3.1) preparing a paste powder: mixing Ni powder and graphene oxide, ball milling, adding sodium carboxymethyl cellulose solution and stirring to obtain a paste powder; S3.2) Applying paste powder: After ultrasonic cleaning and drying the tube body, evenly apply the paste powder on the inner surface of the tube body and then heat and pre-bake; S3.3) Laser cladding treatment: Under argon protection, use laser cladding equipment to perform laser cladding treatment on the paste powder coating.

9. The method for preparing a hydrogen barrier coating for a high-pressure hydrogen transmission titanium alloy pipeline according to claim 1, characterized in that: The step S4 specifically includes: S4.1) Preparation of Ni-La2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5±0.1Pa, the Ni target sputtering power was 150±50W, the La2O3 target sputtering power was 250±50W, and the two targets were sputtered for deposition for 30±10min at the same time; S4.2) Preparation of Si3N4-CeO2 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5±0.1Pa, the Si3N4 target sputtering power was 200±50W, the CeO2 target sputtering power was 250±50W, and the two targets were sputtered for 60±20min at the same time; S4.3) Preparation of Re2O7-Al2O3 layer by magnetron co-sputtering: Ar was used as the ignition gas, both targets were powered by RF power, the coating deposition pressure was 0.5±0.1Pa, the sputtering power of Al2O3 target was 100~150W, the sputtering power of Re2O7 target was 250±50W, and the two targets were sputtered and deposited for 180±30min at the same time; S4.4) Heat insulation treatment: keep the pipe in an Ar gas atmosphere at 500±50°C for 240±60 minutes to complete the preparation of the hydrogen barrier coating for the high-pressure hydrogen transmission titanium alloy pipeline.

10. A titanium alloy high-pressure hydrogen transport pipe comprising a hydrogen barrier coating prepared by the method for preparing a hydrogen barrier coating for a high-pressure hydrogen transport titanium alloy pipeline according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of nickel-phosphorus-based hydrogen-resistant composite coating

    CN116043200A

  • Structure of melted-plated compound coating by vacuum fusion covering+chemical plating and preparation method thereof

    CN110438496A

  • Hydrogen permeation resistant composite vitreous barrier layer for titanium alloy matrix as well as preparation method and application of hydrogen permeation resistant composite vitreous barrier layer

    CN116200742A

  • Hydrogen-resistant coating for hydrogen transmission pipeline and preparation method of hydrogen-resistant coating

    CN116334519A

  • Laminated hydrogen storage material hydrogen storage tank

    CN117967964A